PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS II SDN 004 TERATAK BULUH - Siti Mariyam (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to improve student reading skills by applying the Contextual Teaching and Learning (CTL) learning model in class II. B SDN 004 Teratak Buluh. This research is a class action research that includes planning (action), action (observation), observation (observation), reflection (evaluation) or evaluation. The results showed that the value of students' reading skills for each assessment indicator was in the range of 65% to 85% in the first cycle, which was included in the good and very good category. While the results of the overall reading skills assessment were 71.2% in the good category. The results of students' reading skills in cycle II, the assessment is in the range of 84% to 90% which is included in the category of good and very good, while the results of the overall reading skills assessment in the second cycle are 86.2% with a very good category. Based on these results it can be concluded that the application of the Contextual Teaching And Learning (CTL) learning model can improve the reading skills of students in class II. B SDN 004 Teratak Buluh.